Benthic ostracods (Crustacea) from the Vitória-Trindade Chain, South Atlantic Ocean, with the description of five new species - Luz, Nathalia Carvalho Da; Coimbra, João Carlos (Zootaxa, 2023)
This work is the second part of the analysis of ostracods from the Vitória-Trindade Chain ̶ consisting of four seamounts and Trindade Island—which resulted in the recording of 28 species belonging to 14 genera and eight families. Five new species of Cytherellidae, Bairdiidae, Bythocytheridae, and Xestoleberididae are described in this paper, as follows: Keijcyoidea oceanica sp. nov., Bairdoppilata vitoriensis sp. nov., Vandenboldina kyryia sp. nov., Xestoleberis acuminata sp. nov. and Xestoleberis caperata sp. nov.